Influencing Factors and Purification Performance of a Negative Ion Air Purifier for Indoor Ammonia Gas Removal - Yilin Li; Zewen Liu; Yidong Li; Ying Chen; Ziding Bai; Huaiwang Jing; Ruiyan Zhang; Jianbo Chen (Buildings)
The negative ion air purifier (NIAP) has been used for capturing particulate matter. Nevertheless, the knowledge on its effectiveness in removing other air pollutants such as ammonia gas remains limited. In this study, the effect of an NIAP for indoor ammonia gas removal was evaluated through a series of experimental studies. The applicability and different influencing, operating, and environmental factors on the ammonia gas removal performance were firstly investigated by conducting a series of experiments. Then, in order to understand the performance of the NIAP and the spatial distribution of ammonia gas and other by-products, indoor field measurements of ammonia gas, ozone, and negative ion concentrations in a real bathroom were performed for different cases with the NIAP turned on and off. The results indicated that negative ions were effective in reducing ammonia gas concentration. The operating and environmental factors including upstream wind speed, degree of operating voltage, and initial ammonia gas concentration have great influences on the ammonia gas removal efficiency of the NIAP. The highest removal efficiency can reach to 95.8%, when the upstream wind speed was 0.8 m/s and the degree of operating voltage was at gear 3 (3.0 kV). The purification efficiency of ammonia gas for the NIAP could reach up to 80%.